A NEW APPROXIMATION TO THE DIFFUSION TENSOR AT INOSPHERIC F-LAYER'S ALTITUDE IN THE EQUATORIAL ANOMALY REGION - MOHAMMEDNAJEM, BLAND HASAN (Fırat Üniveristesi, 2017)
Bu çalışmada, Klasik diffüzyon tensörünün (D0, D1, D2 ) elamanları nötr rüzgar hızı(U) ihmal edilerek ve Dünyanın manyetik alanı B=B0z, alınarak ekvator bölgesinde etkin yükseklikler olan (280,300,340,390 410 km) kararlı ve kararsız durumda İyonosferin F- bölgesi için çalışılmıştır. Kalasik diffüzyon katsayılarının büyüklükleri F- bölgesinde hem 12.00 gündüz ve 24.00 gece yerel zamana göre bütün mevsimler için D0> D1> D2 dir. Ancak, D1 ve D2 gündüz geceden daha büyük değerler almaktadır. Bu manyetik ekvatorda electron yoğunluğunun enlemle değişimi ile zıt bir davranış gösterir. Onların bu davranışı elektromanyetik sürüklenme ve dynamo etkisinin bir sonucu olduğu söylenebilir.

In this thesis, the classical diffusion tensor (D0, D1, D2 ) for both steady-state and unsteady-case) for F- region of the ionosphere at the equatorial region is investigated by taking (B=B0z), and by neglecting the neutral winds velocity (U). The calculations were made in the height (280,300,340,390 and 410 km) where the equatorial anomaly was observed predominantly. The magnitudes of the difference of classical diffusion tensor for electrons are D0>D1 >D2 for all seasons with respect to both 12.00LT and 24.00LT at F-region. However, D1 and D2 are bigger during nighttime than daytime and show a behavior reverse to the change with latitude of electron density in the magnetic equator. It is possible to say that the behavior of them can be the result of electromagnetic drift and dynamo effect.
Ekvatoral anormallik bölgesi yüksekliklerinde iyonkürenin F tabakasındaki difüzyon tensörüne yeni bir yaklaşım
Keywords: Fizik ve Fizik Mühendisliği